Internalisasi Nilai Empati Dan Kepedulian Sosial Melalui Kurikulum Cinta - Muhammad Rusydu R (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2026)
National education aims not only to educate the nation but also to shape the character ofstudents, fostering empathy and social awareness. However, the current educational realitydemonstrates a degradation of humanitarian values, characterized by increasingindividualism, minimal tolerance, and rampant bullying in schools. This situation demandsa more humanistic educational approach oriented toward the values of compassion. Thisarticle aims to examine in depth the internalization of empathy and social awareness throughthe "love curriculum" as a character education approach. The study's results indicate thatthe "love curriculum" is an effective means of instilling empathy and social awarenessthrough student-centered learning, teacher role models, positive social interactions, and aninclusive school culture. Thus, the "love curriculum" holds strong relevance in strengtheningcharacter education in Indonesia.